A new forest dwelling button spider from South Africa (Araneae, Theridiidae, Latrodectus) - Wright, B.m.o.g.; Wright, C. D.; Sole, C.l.; Lyle, R.; Tippett, R.; Sholto-Douglas, C.; Verburgt, L.; Engelbrecht, I. (Zootaxa, 2019)
The medically important spider genus Latrodectus Walckenaer 1805, commonly referred to as “button spiders” in South Africa, is represented by six species in the country. Using morphology and the COI barcoding gene we describe a new forest dwelling species, Latrodectus umbukwane n. sp. Wright, Wright, Lyle and Engelbrecht. Females have red markings on both the ventral and posterior dorsal surfaces of the abdomen, parallel spermathecae and three loops of the copulatory ducts. Males have an embolus with four loops and diagnostic white markings on the ventral surface of the abdomen that darken with age. Egg sacs are smooth, large, and bright purple when freshly laid, turning shiny grey with time. Latrodectus umbukwane n. sp. is known only from sand forest vegetation types in northern Zululand, KwaZulu-Natal, South Africa. A predicted geographic distribution for this species is provided based on cartographic mapping of known habitat and altitudinal preference, from which area of occupancy (AOO; 698 km2) and extent of occurrence (EOO; 4963 km2) were calculated to assess potential IUCN Red List status. Due to the uncertainty of the distribution of this species, a Red List status of Data Deficient (DD) is recommended. An updated key to the southern African species of Latrodectus is provided.